Evaluation of restriction endonuclease cleavage of plant nuclear DNA using contaminating chloroplast DNA - Fajkus, J; Reich, J (Folia biologica, 1991)
Plant DNA is often contaminated by chloroplast DNA. The contamination was used here with advantage to check restriction endonuclease cleavage of plant DNA. This method is based on hybridization of Southern blots of digested plant DNA with cloned fragments of chloroplast DNA as a probe. Advantages of this method are demonstrated.
Keywords: rekombinantní DNA; Plants; DNA, Recombinant; Nicotiana; jedovaté rostliny; tabák; Chloroplasts; chloroplasty; polymorfismus délky restrikčních fragmentů; Plants, Toxic; Polymorphism, Restriction Fragment Length; DNA Probes; rostliny; DNA sondy